Cardiovascular benefits outweigh risks in patients with atrial fibrillation in REDUCE-IT (Reduction of Cardiovascular Events with Icosapent Ethyl-Intervention Trial). (14th October 2021) - Olshansky, B; Bhatt, D; Miller, M; Steg, P G; Brinton, E A; Jacobson, T A; Ketchum, S B; Doyle Jr, R T; Juliano, R A; Jiao, L; Kowey, P; Reiffel, J A; et al.
Abstract: Background/Introduction: REDUCE-IT, a multinational, double-blind trial, randomized 8179 statin-treated patients with controlled low density lipoprotein cholesterol, elevated triglycerides, and cardiovascular (CV) risk, to icosapent ethyl (IPE) 4 grams/day or placebo. IPE reduced the primary (CV death, myocardial infarction [MI], stroke, coronary revascularization, hospitalization for unstable angina) and key secondary (CV death, MI, stroke) endpoints 25% and 26%, respectively (each p<0.0001), and individual components including stroke (28%), MI (31%), cardiac arrest (48%), and sudden cardiac death (31%) (all p≤0.01). With IPE, bleeding was greater (11.8% vs 9.9%; p=0.006), serious bleeding trended higher (2.7% vs 2.1%; p=0.06), and atrial fibrillation/flutter (AF/F) hospitalization endpoints increased (3.1% vs 2.1%; p=0.004). Purpose: To evaluate the effects of IPE on the risk of CV events and safety measures in patients by either history of AF/F or in-study occurrence of positively adjudicated AF/F hospitalization. Methods: Conduct post hoc efficacy and safety subgroup analyses of patients with or without either baseline history of AF/F or in-study adjudicated AF/F hospitalization, including hospitalization for ≥24 hours; AF/F not meeting endpoint criteria were reported as adverse events. Results: Patients with (n=751; 9.2%) AF/F history at baseline (vs without; n=7428; 90.8%) (Figure 1), or those with (n=211; 2.6%) positively adjudicated in-study AF/F hospitalization endpoints (vs without; n=7968; 97.4%) (Figure 2), had higher event rates of primary, key secondary, and fatal or nonfatal stroke endpoints, but relative risk reductions with IPE were not significantly different (all interaction p-values [pint]=ns). Similar reductions were observed with IPE across the prespecified endpoint testing hierarchy in patients with or without AF/F history or in-study hospitalization endpoints. Patients with baseline AF/F history had similar relative risk for in-study occurrence of AF/F hospitalization with IPE versus placebo (pint=0.21) but had greater absolute risk (12.5% vs 6.3%, IPE vs placebo) vs patients without baseline AF/F history (2.2% vs 1.6%, IPE vs placebo); i.e., recurrent AF/F in those with a prior history of AF/F was more prevalent than de novo AF/F. Serious bleeding trended higher regardless of AF/F history or in-study AF/F hospitalization endpoints (all pint=ns); absolute risk of serious bleeding was greater in patients with AF/F history at baseline (7.3% vs 6.0%) vs those without a baseline history of AF/F (2.3% vs 1.7%), and serious bleeding also trended higher in patients with in-study AF/F hospitalization (8.7% vs 6.0%) vs without (2.5% vs 2.0%) [all IPE vs placebo]. Conclusion: REDUCE-IT patients with AF/F history or in-study AF/F hospitalization endpoints had greater CV risk, but similar relative risk reduction in primary, key secondary, and fatal or nonfatal stroke endpoints with IPE. FUNDunding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Amarin Pharma, Inc.